Comparison of Nesting Features and Breeding Success of Turtle Dove Streptopelia turtur between Orchards and Riparian Habitats - Mansouri, Ismail; Squalli, Wafae; El Agy, Abdelbari; El-Hassani, Abderahim; El Ghadraoui, Lahcen; Dakki, Mohamed (International Journal of Zoology, 2021)
The European turtle dove Streptopelia turtur breeds in both farmlands and woodlands, and it is important to explore the difference in breeding ecology of this threatened game in these two ecosystem types. This study, carried out during four years (2015–2018), compares nesting features of this species and its breeding success between apple orchards and riparian vegetation in Midelt Province, Morocco. The main result revealed that the nest placement, including nesting-tree height and nest height, is similar between orchards and riparian trees. However, the nest dimensions (big and small diameters) were larger in orchards. Correlations were variable among nest placement parameters and dimensions. On the contrary, in four breeding seasons, where 566 nests were monitored (467 in orchards and 99 in riparian sites), the average breeding success was different (57% of chicks in apple farms and 53% in riparian vegetation). Moreover, in apple orchards, clutches’ failure is due to both predation (18.89% of eggs and 10.54% of chicks) and temperature lowering (5.03% of unhatched eggs and 5.49% of dead chicks), while in riparian vegetation, the loss is due to nest desertion (21.33% of clutches) and mostly predation (33.16% of clutches).